A Study on Students’ Disruptive Behaviors in English Online Classroom and Its Solution by the Lecturers - Sastika Seli; Dewi Syafitri; Ayu Oktaviani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to explain the views of lecturers and students of STKIP-PGRI Lubuklinggau on disruptive behavior in online English learning during the Covid 19 pandemic and describe the level of seriousness in providing the best solution to these problems. The research method used is descriptive qualitative research using grounded theory with an inductive approach. Data was collected through interviews as primary data, observation and document analysis. The subjects of this study were seven lecturers and 14 students (disruptive behavior) English Education STKIP-PGRI Lubuklinggau. The results showed seven general categories of disruptive behavior: breaking time, dishonesty, disrespect, lack of concentration, skipping lessons and assignments, doing things privately, and giving slow responses. The lecturers offered several solutions for these problems by considering the level of seriousness, such as applying positive discipline, formulating and designing rules strategies and teaching media, giving punishment and expecting to end online learning. In conclusion, by knowing students' disruptive behavior, lecturers and other parties will be more concerned about taking some appropriate actions to minimize and avoid some behaviors in improving online English learning. Keywords: Disruptive Behavior, Discipline Problems, Online Learning, Teaching in a Pandemic Period